2013
DOI: 10.1371/journal.pntd.0002426
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Tungiasis and Tungiasis-Associated Morbidity Using the Plant-Based Repellent Zanzarin: A Randomized, Controlled Field Study in Rural Madagascar

Abstract: BackgroundTungiasis, a parasitic skin disease caused by the female sand flea Tunga penetrans, is a prevalent condition in impoverished communities in the tropics. In this setting, the ectoparasitosis is associated with important morbidity. It causes disfigurement and mutilation of the feet. Feasible and effective treatment is not available. So far prevention is the only means to control tungiasis-associated morbidity.MethodologyIn two villages in Central Madagascar, we assessed the efficacy of the availability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 27 publications
1
42
0
2
Order By: Relevance
“…21 However, a randomized controlled study in rural Madagascar showed that the regular wearing of shoes had a significantly lower effect on the attack rate and on the regression of tungiasis-associated inflammation than the regular application of a repellent based on coconut oil when compared with a control group without intervention. 16 Our study also shows that the availability of closed shoes does not guarantee that the shoes are worn regularly by their owners. One reason relevant to this case series is that individuals with severe tungiasis-associated morbidity refrain from wearing closed shoes, because this increases their pain.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…21 However, a randomized controlled study in rural Madagascar showed that the regular wearing of shoes had a significantly lower effect on the attack rate and on the regression of tungiasis-associated inflammation than the regular application of a repellent based on coconut oil when compared with a control group without intervention. 16 Our study also shows that the availability of closed shoes does not guarantee that the shoes are worn regularly by their owners. One reason relevant to this case series is that individuals with severe tungiasis-associated morbidity refrain from wearing closed shoes, because this increases their pain.…”
Section: Discussionmentioning
confidence: 74%
“…The social and economic characteristics of the study area have been described elsewhere. 16 Study population and study design. When preparing an intervention study involving several communities in Moramanga district, we identified eight individuals with an extremely high intensity of infestation (more than 75 sand flea lesions).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides, many families cannot afford shoes for all household members. A detailed description of the study area and population has been published elsewhere [13].…”
Section: Study Area and Study Populationmentioning
confidence: 99%